Системы жидкой циркуляционной смазки Ж-1, Ж-2 прокатного стана НТЛС "1680" ОАО "Запорожсталь" - Татьков, В. В.; Музыкин, Юрий Дмитриевич; Путноки, А. Ю.; Мацко, С. В.; Москаленко, П. П.; Мудрицкий, С. А.; Новоселов, Ю. В. (НТУ "ХПИ", 2015)
Рассмотрены вопросы обеспечения устойчивой работы системы жидкой циркуляционной смазки для шестеренных клетей и силовых редукторов главных приводов рабочих клетей листопрокатного стана НТЛС «1680». Приведена гидравлическая схема смазочных станций Ж-1 и Ж-2, а также показаны параметры, контролируемые в процессе работы как с помощью мнемосхем, так и аналоговых приборов. Предложенные схемы смазки обеспечивают поддержание расчетных режимов работы в парах трения за счет бесперебойной подачи смазочного материала во все трущиеся сопряжения.

The problems of ensuring the stable operation of liquid circulation lubrication for gear reducers and power stands main drives work stands plate rolling mill «1680». The proposed system of fluid circulation lubrication meet modern requirements of both specifications, the maintenance of which is carried out in an automatic mode, and on safety regulations for large hydraulic system. Operating considered oil systems on a continuous hot rolling mill thin sheet of «1680» showed their high reliability and availability of the management due to the high degree of automation and the availability of reliable control of almost all the operating parameters. Shows a hydraulic circuit and a lubricating unit, and also shows the parameters monitored during operation by both mimics and analog devices. Rational arrangement of mnemonic circuits and control panels allows for the maintenance of accounting modes in pairs of friction due to a continuous supply of lubricant to all the friction coupling.
System liquid circulating lubrication G-1, G-2 time of the rolling mill "1680" JSC "Zaporizhstal"
Keywords: клеть шестеренная; схема гидравлическая; трение; сопряжение; hydraulic circuit; lubrication system; friction; mate